Outside the paint : when basketball ruled at the Chinese playground - Yep, Kathleen S. (Philadelphia : Temple University Press, 2009)
Breaking out of Chinatown by shooting and dribbling.
Introduction -- 1 The Chinese Playground -- 2 The Hong Wah Kues Discover America -- 3 The Mei Wahs Knew How to Use Their Elbows and Push -- 4 "Mr. Chinese Cager" Plays Madison Square Garden -- 5 Helen Wong and the "Muscle Molls" -- Conclusion: The Chinese Playground and Yao Ming in the Era of Globalized Sports
Includes bibliographical references (pages 163-190) and index.
Description based upon online resource; title from PDF title page (viewed May 11th, 2024).
JSTOR
Keywords: Basketball -- California -- San Francisco; Playgrounds -- California -- San Francisco; Chinese Americans -- California -- San Francisco; Chinatown (San Francisco, Calif.); Basketball -- United States -- History; Basket-ball -- Californie -- San Francisco; Américains d'origine chinoise -- Californie -- San Francisco; SPORTS & RECREATION -- Basketball; SOCIAL SCIENCE -- General; Basketball; Chinese Americans; Playgrounds; California -- San Francisco; California -- San Francisco -- Chinatown; United States; History